Transcript Levels of Aldo-Keto Reductase Family 1 Subfamily C (AKR1C) Are Increased in Prostate Tissue of Patients with Type 2 Diabetes - Andras Franko (Journal of Personalized Medicine, 2020)
Aldo-keto reductase family 1 (AKR1) enzymes play a crucial role in diabetic complications. Since type 2 diabetes (T2D) is associated with cancer progression, we investigated the impact of diabetes on AKR1 gene expression in the context of prostate cancer (PCa) development. In this study, we analyzed benign (BEN) prostate and PCa tissue of patients with and without T2D. Furthermore, to replicate hyperglycemia in vitro, we treated the prostate adenocarcinoma cell line PC3 with increasing glucose concentrations. Gene expression was quantified using real-time qPCR. In the prostate tissue of patients with T2D, AKR1C1 and AKR1C2 transcripts were higher compared to samples of patients without diabetes. In PC3 cells, high glucose treatment induced the gene expression levels of AKR1C1, C2, and C3. Furthermore, both in human tissue and in PC3 cells, the transcript levels of AKR1C1, C2, and C3 showed positive associations with oncogenes, which are involved in proliferation processes and HIF1α and NFκB pathways. These results indicate that in the prostate glands of patients with T2D, hyperglycemia could play a pivotal role by inducing the expression of AKR1C1, C2, and C3. The higher transcript level of AKR1C was furthermore associated with upregulated HIF1α and NFκB pathways, which are major drivers of PCa carcinogenesis.